Pengembangan E-Modul Interaktif Berbasis Case Study Pada Materi Sistem Sirkulasi Darah Untuk Siswa Kelas XI SMA - Septia, Adela Eka; Hamidah, Afreni; Sadikin, Ali (UNIB Press, 2024)
The development of science and technology in Indonesia encourages educational innovation, including the use of technology in learning according to the Independent Curriculum. The printed module used is less effective in visualizing biological processes. This research aims to develop learning media, namely an interactive e-module based on a case study of blood circulation system material, then analyzing the suitability of the media, analyzing teacher and student perceptions of the product that has been developed. This research is development research (Research and Development) using the ADDIE development model which consists of Analyze, Design, Develop, Implement and Evaluation. The types of data for this research are qualitative and quantitative. The data collection instruments used were validation questionnaires from material experts and media experts to determine the suitability of the product, teacher and student perception questionnaires which were distributed to small groups of 6 students and large groups of 27 students. The research results show that case study-based interactive e-modules that have gone through the material validation stage obtained a percentage of 91.6% in the